Confirmation of the factorial structure of the Japanese short version of the TEMPS-A in psychiatric patients and general adults - Nakato Y; Inoue T; Nakagawa S; Kitaichi Y; Kameyama R; Wakatsuki Y; Kitagawa K; Omiya Y; Kusumi I (Neuropsychiatric Disease and Treatment, 2016)
Yasuya Nakato,1 Takeshi Inoue,1,2 Shin Nakagawa,1 Yuji Kitaichi,1 Rie Kameyama,1 Yumi Wakatsuki,1 Kan Kitagawa,1 Yuki Omiya,1 Ichiro Kusumi1 1Department of Psychiatry, Hokkaido University Graduate School of Medicine, Sapporo, 2Department of Psychiatry, Tokyo Medical University, Tokyo, Japan Background: The Temperament Evaluation of the Memphis, Pisa, Paris, and San Diego Auto-questionnaire (TEMPS-A) is a 110-item questionnaire that assesses five affective temperaments. However, a valid shortened version is desired for large-scale investigations to enhance the compliance of respondents. Methods: A confirmatory factor analysis was conducted among 320 psychiatric patients and 61 general adults. The participants completed the Japanese 39-item short version of the TEMPS-A, and a portion of the participants completed the 110-item version. An exploratory factor analysis with the principal factor method and varimax rotation was conducted to identify a more suitable model of the short version of the TEMPS-A. Results: The confirmatory factor analysis revealed that the 39-item version exhibited a poor model fit. However, we found that the 18-item version exhibited a firm five-factor structure based on the exploratory factor analysis, and this model exhibited an acceptable model fit. It had good or acceptable internal consistency (Cronbach’s αs: 0.672–0.819). Limitations: The majority of the subjects in the present study were patients, and the temperament data may have been affected by psychiatric symptoms. Conclusion: A firm five-factor structure was not found in the 39-item short version of the Japanese TEMPS-A. Therefore, an 18-item version was proposed. This new 18-item version of the TEMPS-A might be useful for clinical applications and large-scale investigations. Keywords: TEMPS-A, affective temperament, depression, validation, confirmatory factor analysis Corrigendum for this paper has been published